(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
The guide qualification is very popular in Hungary. The participants of the course are dissimilar, taking into consideration their age and qualification. The hypothesis said, the reason of the popularity is only the interesting side of a guide’s work. Other reason could be economic and exploying doubts nowadays, and this is equal to a motivation effect, therefore people spend money and leisure time on learning in an adult education school. Nowadays adult educating system is not suitable for the competition in this field, and do not take into consideration the practical side of the education. The results of the final exams confirms the same theory, and the average competences can not growth during the course time, theefore students without higher education degrees still have disadvantages.